Phase Variation During Host Colonization and Invasion by Campylobacter jejuni and Other Campylobacter Species - Cayrou, Caroline; Barratt, Natalie A.; Ketley, Julian M.; Bayliss, Christopher D. (Frontiers in Microbiology, 2021)
Phase variation (PV) is a phenomenon common to a variety of bacterial species for niche adaption and survival in challenging environments. Among Campylobacter species, PV depends on the presence of intergenic and intragenic hypermutable G/C homopolymeric tracts. The presence of phase-variable genes is of especial interest for species that cause foodborne or zoonotic infections in humans. PV influences the formation and the structure of the lipooligosaccharide, flagella and capsule in Campylobacter species. PV of components of these molecules is potentially important during invasion of host tissues, spread within hosts and transmission between hosts. Motility is a critical phenotype that is potentially modulated by PV. Variation in the status of the phase-variable genes has been observed to occur during colonization in chickens and mouse infection models. Interestingly, PV is also involved in bacterial survival of attack by bacteriophages even during chicken colonization. This review aims to explore and discuss observations of PV during model and natural infections by Campylobacter species and how PV may affect strategies for fighting infections by this foodborne pathogen.